Redefining the major peanut allergens - Zhuang, Yonghua (Immunol Res, 2013)
Food allergy has become a major public health concern in westernized countries, and allergic reactions to peanuts are particularly common and severe. Allergens are defined as antigens that elicit an IgE response, and most allergenic materials (e.g., pollens, danders, and foods) contain multiple allergenic proteins. This has led to the concept that there are “major” allergens and allergens of less importance. “Major allergens” have been defined as allergens that bind a large amount of IgE from the majority of patients and have biologic activity. However, the ability of an allergen to cross-link complexes of IgE and its high-affinity receptor FcεRI (IgE/FcεRI), which we have termed its allergic effector activity, does not correlate well with assays of IgE binding. To identify the proteins that are the most active allergens in peanuts, we and others have employed in vitro model assays of allergen-mediated cross-linking of IgE/FcεRI complexes and have demonstrated that the most potent allergens are not necessarily those that bind the most IgE. The importance of a specific allergen can be determined by measuring the allergic effector activity of that allergen following purification under non-denaturing conditions and by specifically removing the allergen from a complex allergenic extract either by chromatography or by specific immunodepletion. In our studies of peanut allergens, our laboratory has found that two related allergens, Ara h 2 and Ara h 6, together account for the majority of the effector activity in a crude peanut extract. Furthermore, murine studies demonstrated that Ara h 2 and Ara h 6 are not only the major elicitors of anaphylaxis in this system, but also can effectively desensitize peanut-allergic mice. As a result of these observations, we propose that the definition of a major allergen should be based on the potency of that allergen in assays of allergic effector activity and demonstration that removal of that allergen from an extract results in loss of potency. Using these criteria, Ara h 2 and Ara h 6 are the major peanut allergens.